Human-elephant conflict in the African rainforest landscape: crop-raiding situations and damage mitigation strategies in rural Gabon - Matsuura, Naoki; Nomoto, Mayuko; Terada, Saeko; Yobo, Christian Mikolo; Memiaghe, Hervé Roland; Moussavou, Guy-Max (Frontiers in Conservation Science, 2024)
While the conservation of forest elephants is a global concern, human-elephant conflict (HEC), especially crop-raiding by elephants, is a serious threat to both human livelihoods and conservation efforts. However, only a few studies have explored elephant crop-raiding and related damage mitigation strategies in Central Africa's forest landscapes, which are characterized by low human and high animal densities and shifting cultivation practices. This study investigates HEC in rural Gabon, where human activities are limited, and local livelihoods are severely threatened by crop-raiding elephants. Through long-term ethnographic research and an in-depth analysis of damage mitigation practices by local people, the study unveils serious crop-raiding by elephants, leading to a significant change in the local lifestyle. Most households spend the majority of days in the field protecting crops, resulting in the village becoming almost empty. In addition to the physical burden of staying in poor living conditions, there is a considerable psychological burden for local people. Establishing effective elephant conservation systems requires understanding each local situation and evaluating the various costs to local people. To sustain livelihoods and address the challenge of HEC, it is crucial for local communities and various stakeholders to act collectively. 削除: Not only local people but also various stakeholders should 31 take up the responsibility for sustainable local development for 32 implementing elephant conservation.